2000
DOI: 10.1007/bf03028096
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the milling characteristics of Al-SiC particulate composites

Abstract: The present investigation focuses on the face milling characteristics of LM25A1 -SiC particulate composites produced through stir casting. Experiments were conducted according to an L27 orthogonal array and mathematical models were developed for such machining characteristics as flank wear, specific energy and surface roughness whose adequacy was checked. The insignificant effects present in the models were eliminated using a t-test. Goal programming was employed to optimize the cuv.ing conditions by consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The addition of a ceramic reinforcement phase in monolithic metal alloys significantly alters their mechanical and physical properties, as well as their deformation behavior [9][10][11][12]. The Aluminum LM25 alloy is of low density and high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of a ceramic reinforcement phase in monolithic metal alloys significantly alters their mechanical and physical properties, as well as their deformation behavior [9][10][11][12]. The Aluminum LM25 alloy is of low density and high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2. From the results it is inferred that tool wear is influenced by speed and feed rate than other machining parameters [6,15].It clear that as speed increases, the flank wear increases, it is because, the increase in cutting speed increases the impact load on the work material by the insert due to the increased kinetic energy which cause a steady state increase in wear with speed assisted by the increased temperature at the interface. Similarly, as the feed increases flank wear increases owing to increase in force and work done in turn causes increase in heat generation and thermal load per cutting edge…”
Section: Rsm-based Predictive Modelsmentioning
confidence: 91%
“…Saeed chavosi [5] has investigated the effects of feed, depth of cut, and cutting speed on flank wear of Tungsten carbide and PCD inserts in CNC turning of 7075 Al Alloy with 10 % wt SiC Composites. Karthikeyan et al [6] has optimized the milling characteristics (Flank wear, Specific energy, and surface roughness) of Al-SiC particulate composites using goal programming technique and examined that volume fraction of SiC particles present in the aluminum alloy matrix has a significant effect on the milling characteristics increasing tool wear and specific energy and decreasing surface roughness. El-Gallab and Sklad [7] studied the surface integrity of Al/SiC particulate MMCs and concluded that surface roughness and flank wear increases with increase in the feed rate and cutting speed.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that built-up edge occurs ideally at low cutting speeds [113]. Many studies suggest that the controlled formation of a built-up edge will result in an extension of the useful tool life during machining by protecting the tool from abrasive wear [41,[114][115][116]. It is suggested that the built-up edge protects the tool from the abrasive particle wear caused by the dispersed phase, acting as a sacrificial coating that is constantly replenished as the metal matrix is machined [85] [42].…”
Section: Built-up Edgementioning
confidence: 99%